Structural Evolution of Colloidal Crystal Films in the Process of Melting Revealed by Bragg Peak Analysis; Langmuir; Vol. 31 (19) - Sulyanova E. A. Elena; Shabalin A. Anatoly; Zozulya A. V. Alexey; Meijer Janne-Mieke; Dzhigaev D. Dmitry; Gorobtsov O. Oleg; Kurta R. P. Ruslan; Lorenz U. Ulf; Singer A. Andrej; Lazarev S. V. Sergey Vladimirovich; Yefanov O. Oleksandr; Zaluzhnyy I. Ivan; et al. (2015, 2015)
Title screen